Nutrition: the obesity deciding factor - María de Lourdes Rodríguez-Pérez; Pedro Aciel Díaz-Rodríguez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
This research of bibliography revision type is directed to highlight the important relationship there is between nutrition and obesity. According to specialists, changes on feeding and life style that that accompany the urbanity and the society development have favored the gens expression that predisposes obesity, and the sometime, has modified the health and disease patterns which are associated with people morbidity increasing and their life hope decreasing. It can be marked that obesity is a complex, multifactorial disease, with alteration on appetite regulation and energetic metabolism. In spite of its etiology is not clear enough, among the most important factors that seen to be associated with the disease appearance are included the genetic, environmental, hormonal and neurochemical, besides psychosocial and cultural ones.